2006
DOI: 10.1111/j.1442-2042.2006.01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Naftopidil monotherapy vs naftopidil and an anticholinergic agent combined therapy for storage symptoms associated with benign prostatic hyperplasia: A prospective randomized controlled study

Abstract: Aim:The aim of this study was to compare the efficacy and safety of α 1 -adrenoceptor (α 1 -AR) antagonist monotherapy with combination therapy using α 1 -AR antagonist and anticholinergic agent for benign prostatic hyperplasia (BPH) with storage symptoms as the chief complaint. Methods: In this prospective comparative study, either 25-75 mg/day of naftopidil monotherapy (monotherapy group) or combination therapy using 25-75 mg/day of naftopidil and an anticholinergic agent (10-20 mg/day of propiverine hydroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…[107][108][109] A Japanese study also found that combination therapy improved storage symptoms, especially urgency, in BPH. 110 In a 12-week trial of combination therapy in men with LUTS, the benefits were significantly greater in the combination therapy group, with only a mild increase in residual urine volumes, and a 1% incidence of urinary retention, with no difference between groups. 111 It should be noted , however, that most of these studies were conducted with Caucasian men with strict exclusion criteria, specialists' supervision, and relatively short-term observational period.…”
Section: Grade Of Recommendation: Reservedmentioning
confidence: 98%
“…[107][108][109] A Japanese study also found that combination therapy improved storage symptoms, especially urgency, in BPH. 110 In a 12-week trial of combination therapy in men with LUTS, the benefits were significantly greater in the combination therapy group, with only a mild increase in residual urine volumes, and a 1% incidence of urinary retention, with no difference between groups. 111 It should be noted , however, that most of these studies were conducted with Caucasian men with strict exclusion criteria, specialists' supervision, and relatively short-term observational period.…”
Section: Grade Of Recommendation: Reservedmentioning
confidence: 98%
“…In this context, Maruyama and colleagues 24 (Table 1) compared the efficacy and safety of naftopidil monotherapy to its combination with anticholinergic agents. In this 12 week RCT, 101 BPH/LUTS patients were randomly divided in two groups treated with either naftopidil monotherapy (25-75 mg/day, n ¼ 53) or naftopidil plus an anticholinergic agent (propiverine hydrochloride 10-20 mg/day or oxybutynin hydrochloride 2-6 mg/day, n ¼ 48).…”
Section: Studies Of Naftopidil Plus Antimuscarinic Agentsmentioning
confidence: 99%
“…Two studies compared low (25 mg/day) versus high (75 mg/day) dose naftopidil 22 , and 25 mg naftopidil thrice-a-day versus 75 mg/day 23 . Further studies compared naftopidil monotherapy to naftopidil plus either of two antimuscarinic agents, oxybutynin or propiverine 24,25 . Finally, eleven trials 12,14,17-25 used a parallel treatment design and three trials 13,15,16 used a crossover design (Table 1).…”
Section: Randomized Clinical Trials (Rcts) In Bph-associated Lutsmentioning
confidence: 99%
“…Recently, solid evidence to support the efficacy and safety of combination of α1-blockers and anticholinergic agents for male LUTS associated OAB has been reported 4245. Maruyama et al compared the efficacy and safety of naftopidil monotherapy with combination therapy using naftopidil and anticholinergic agents for patients having LUTS/BPH with storage symptoms 46. Either monotherapy with 25–75 mg of naftopidil (n = 45) or combination therapy using 25–75 mg of naftopidil and an anticholinergic agent (10–20 mg of propiverine hydrochloride or 2–6 mg of oxybutynin hydrochloride, n = 41) was randomly given to 101 patients with LUTS/BPH with IPSS ≥ 8, QOL index ≥ 3, a score for day frequency ≥ 3, and a score for nocturia ≥ 2 for 12 weeks.…”
Section: Effect Of Naftopidil On Overactive Bladder Symptoms and Noctmentioning
confidence: 99%